2016
DOI: 10.1111/dth.12410
|View full text |Cite
|
Sign up to set email alerts
|

New approach in the treatment of refractory vitiligo: CO2 laser combined with betamethasone and salicylic acid solution

Abstract: The aim of this study is to evaluate the use of fractional carbon dioxide laser (CO ) with betamethasone and salicylic acid solution in the treatment of patients with refractory vitiligo in hands. Each hand of the patient was randomly assigned to one of two groups: lesion treated with fractional carbon dioxide laser associated with betamethasone and salicylic acid solution administration or lesion treated only with betamethasone and salicylic acid solution. We conclude that combined treatment with fractional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 12 publications
2
25
0
1
Order By: Relevance
“…Studies have shown that the treatment with fractional CO 2 laser combined with topical betamethasone or salicylic acid could effectively and safely be used in the treatment of vitiligo (Cunha, Scabine, Bonati, & Salai, 2016;Li et al, 2015).However, our study suggests that the triple treatment failed to achieve superior repigmentation or better patient satisfaction. We suggest that the reasons for the relative treatment failure are as follows.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Studies have shown that the treatment with fractional CO 2 laser combined with topical betamethasone or salicylic acid could effectively and safely be used in the treatment of vitiligo (Cunha, Scabine, Bonati, & Salai, 2016;Li et al, 2015).However, our study suggests that the triple treatment failed to achieve superior repigmentation or better patient satisfaction. We suggest that the reasons for the relative treatment failure are as follows.…”
Section: Discussionmentioning
confidence: 57%
“…The fractional CO 2 laser creates microscopic vertical canaliculi known as “microscopic treatment zones” (MTZ), leading to a fractional disruption of the epidermal barrier, which will allow the penetration of certain topically applied drugs. Studies have shown that the treatment with fractional CO 2 laser combined with topical betamethasone or salicylic acid could effectively and safely be used in the treatment of vitiligo (Cunha, Scabine, Bonati, & Salai, 2016; Li et al, 2015). However, our study suggests that the triple treatment failed to achieve superior repigmentation or better patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 6 trials, 2 were from Thailand (4, 5), and 1 from each of the following countries: Brazil (6), Iran (8), Lebanon (7) and Korea (3). Five studies adopted the quartile grading scale for clinical assessment (3)(4)(5)(6)(7). The mean disease duration varied from 3.6 to 16.8 years.…”
Section: Literature Search and Study Characteristics And Qualitymentioning
confidence: 99%
“…Lasers are a popular treatment modality for a myriad of dermatological conditions. In recent years, fractional CO 2 laser has been introduced as an add-on treatment for vitiligo (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Fractionated ablative laser represents a new modality for skin resurfacing based on the theory of fractional photothermolysis (13).…”
mentioning
confidence: 99%
“…To date, most of the studies evaluated laser microporation in vitro or in vivo (animal studies).There are few clinical studies assessing the efficacy of microporation in human [11,12] .…”
Section: Laser Microporationmentioning
confidence: 99%